Regulatory roles of epigenetic modulators, modifiers and mediators in lung cancer. (February 2017) - Shi, Lin; Zheng, Minghuan; Hou, Jiayuan; Zhu, Bijun; Wang, Xiangdong
Abstract: Lung cancer as the leading cause of cancer-related deaths can be initiated and progressed by the interaction between dynamically genetic and epigenetic elements, although mechanisms mediating lung cancer development and progression remain unclear. Tumor progenitor genes may contribute to lung carcinogenesis and cancer progression, are epigenetically disrupted at the early stages of malignancies even before mutations, and alter cell differentiation throughout tumor evolution. The present review explores potential roles and mechanisms of epigenetic modulators, modifiers and mediators in the development of lung cancer. We also overviewed potential mechanisms by which epigenetic modulators, modifiers and mediators control and regulate 3D nuclear architectures, and discussed translational efforts to epigenetic modifications for treatment of lung cancer. Deep understanding of epigenetic modulators, modifiers and mediators will benefit the discovery and development of new diagnostics and therapies for lung cancer.